Canal virtual de tempo-real - Panont, Fernando Sales (Universidade Federal de São Carlos, 2006)
Due to the increase of general purpose operational systems support for real-time applications and by the increasing number of network interfaces with multiple communication technologies present in one single computational device, a middleware, with real-time characteristics, was designed and developed. This middleware encapsulates these communication technologies and protocols in order to improve fault tolerance and consequentially comply with deadlines for message transmission through connectivity options supply. Moreover, the Real Time Virtual Channel provides a virtual access point address mechanism, where each address maps a set of real access points from the consumer endpoint. For the translation of these addresses in real access points, name servers, known as Brokers, were also implemented.
Keywords: Tempo real; Rede de computadores; Protocolos de comunicação; Sistemas de transmissão de dados; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO